Construct validation of the Test of Emotional Intelligence (TEMINT): a two-study investigation - Blickle, Gerhard; Momm, Tassilo; Liu, Yongmei; Witzki, Alexander; Steinmayr, Ricarda (European journal of psychological assessment, 2011)
This research seeks to further validate the Test of Emotional Intelligence (TEMINT), an ability-based measure of emotional reasoning skills that has accrued an impressive record of validating evidence. With a sample of 192 university students, Study 1 showed that TEMINT was associated most closely with the “understanding emotion” branch of the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT - Mayer, Salovey, & Caruso, 2002). Study 2 was a longitudinal study with 71 employees over 2 years. TEMINT moderated both the getting-ahead motive - income relationship, and the getting-ahead motive - perceived marketability relationship, giving empirical support to the social facilitator role of emotional reasoning skills. Implications and limitations are discussed.